Participatory Development of a 3D Telemedicine system during Covid: the future of remote consultations - Fowers, Spencer; Spina, Thiago V.; Britto Mattos Lima, Andrea; Cutler, Ben; Tittsworth, David; Shepperd, Mike; Chang, Wayne; Hoak, Amber; Johnson, Johnny; Hudson, Whitney (Journal of Plastic, Reconstructive & Aesthetic Surgery, 2022)
Background The Covid pandemic brought the need for more realistic remote consultations into focus. 2D telemedicine solutions fail to replicate the fluency or authenticity of in-person consultations. This research reports on an international collaboration on the participatory development and first validated clinical use of a novel, real-time 360-degree 3D Telemedicine system worldwide. Development of the system - leveraging Microsoft's HoloportationTM communication technology – commenced at Canniesburn Plastic Surgery Unit, Glasgow in March 2020. Methods Research followed VR CORE guidelines on development of Digital Health trials, placing patients at the heart of the development process. This consisted of three separate studies - a clinician feedback study (23 clinicians, Nov-Dec 2020), a patient feedback study (26 patients, Jul-Oct 2021), and a cohort study focusing on safety and reliability (40 patients, Oct 2021 - Mar 2022). “Lose, Keep and Change” feedback prompts were used to engage patients in the development process and guide incremental improvements. Results Participatory testing demonstrated improved patient metrics with 3D in comparison to 2D Telemedicine, including validated measures of satisfaction (p<0.0001), realism or ‘presence’ (Single Item Presence scale, p<0.0001), and quality (Telehealth Usability Questionnaire, p=0.0002). Safety and clinical concordance (95%) of 3D Telemedicine with a face-to-face consultation were equivalent or exceeded estimates for 2D Telemedicine. Conclusions One of the ultimate goals of telemedicine is for the quality of remote consultations to get closer to the experience of face-to-face consultations. These data provide the first evidence that HoloportationTM communication technology brings 3D telemedicine closer to this goal than a 2D equivalent. Keywords Telemedicine 3 dimensional remote consultation Plastic Surgery Covid 19 presence realism